Comparative Legal Perspectives on Cultural Land Trusts for Urban Spaces of Culture, Community, and Art: A Tool for Counteracting Displacement (Milan Law Review, 2021)
As cities redevelop and previously less desirable or marginalized portions of the city space are “retaken” by a city, areas that have provided affordable performance, rehearsal, and live/work space for the arts and culture sector are becoming increasingly less available for these uses. Focusing predominantly on the Canadian Civil Law and Common Law context with passing reference to other jurisdictions such as the US, Scotland, and the UK, this article explores techniques for managing the increased pressure on and increasingly rapid displacement of spaces of arts, culture, and community cultural wealth that is taking place in cities. To this end, in assessing newly adopted municipal and provincial cultural strategies that are intended to amplify and promote these same spaces that are being displaced as well as even more recent COVID-19 recovery plans for art and culture in cities, this article will narrow in on the potential application of the community-led cultural land trust structure.
Keywords: Land Trusts; Property Law; Cultural Heritage Law; Comparative Law; Urban Law; Urban Redevelopment; Cities; Culture; Displacement